An old picture … or is it? The relations between business and political networks in Hungary. Issue 3 (17th October 2016) - Mandják, Tibor; Simon, Judit
Abstract : Purpose: The purpose of this paper is to address two questions: how do business and political (i.e. party politics and state) networks relate? What are the consequences of the relations between these two networks for the behaviour of the actors involved? Design/methodology/approach: The research design consists of the historical approach based on relevant literature sources of the past, a relatively long period – from 1968, the beginning of the era of market socialism, until the first decade of the twenty-first century, by which time the market economy had been established for more than 20 years. The authors analyse the behaviour of economic and non-economic actors in Hungary based on cases and historical data, applying the IMP network approach. Findings: Research findings demonstrate the long-term influence of the relation between business and bureaucratic networks on managerial and organizational network behaviour. The old and new pictures of the economic system are different, but the background to the pictures and the movement in the two pictures are quite similar. Research limitations/implications: The historical illustrations and cases the authors have presented cannot be too widely generalized: the characteristics of the Hungarian mode of transition from market socialism to market economy impose important limitations on the generalizability of the findings. Practical implications: The study offers lessons to policy makers: policy decisions can have long term, unanticipated impacts on non-target areas as well. Social implications: The results confirm that the informal networks of socialism can replicate themselves and network structures can be repurposed in the system after the transition as well. Originality/value: One contribution of the paper is related to the second network paradox: the cases illustrate non-business relationships with non-economic factors, particularly relations with bureaucracy. The other contribution is the description of how the transition from socialism to capitalism affected the networks that firms were embedded in before and after the transition.